The impact of using different ancestral reference populations in assessing crossbred population admixture and influence on performance - Jaafar, Mohd A.; Heins, Bradley J.; Dechow, Chad; Huson, Heather J. (Frontiers in Genetics, 2022)
Crossbreeding is a process in which animals from different breeds are mated together. The animals produced will exhibit a combination of additive and non-additive genetic improvement from parental breeds. However, crossbreeding may also breakup the unique and beneficial gene combinations in parental breeds. This effect of crossbreeding is still poorly understood with respect to 3-breed crossbreeding systems. This study examined variation in genomic ancestry estimations relative to pedigree-based estimations and correlated breed composition to key traits. Two rotational crossbred populations (n=607), ProCROSS and Grazecross were assessed. ProCROSS is a product of rotational crossbreeding of Viking Red (VKR), Holstein (HOL), and Montbeliarde (MON). Grazecross consists of Viking Red (VKR), Normande (NOR), and Jersey (JER). Both programs capitalized on the effect of heterosis. The VKR is a marketing term for Swedish Red, Danish Red, and Finnish Ayrshire breed, complicating breed determination. Therefore, genomic breed composition estimates were compared using two different representations of VKR, one was based on parents used in the crossing system and a second based on VKR ancestral breed genotypes. Variation of breed composition estimates were assessed between pedigree and genome-based predictions. Genomic estimations were correlated with production and health traits by comparing extreme performance groups to identify the relationship between breed ancestry and performance. With the exception of the JER breed in Grazecross, all other estimates of the purebred contribution to the ProCROSS and Grazecross showed a significant difference in their genomic breed estimation when using the VKR ancestral versus the parental reference populations for analysis. These observations were expected given the different relationship of each VKR representation to the crossbred cattle. Further analysis showed that regardless of which VKR reference population was used, the degree of MON and HOL breed composition plays a significant role in ProCROSS milk and fat production, while the degree of VKR and NOR ancestry were related to improved Grazecross health performance. In all, identifying the most appropriate animals to use as reference in admixture analysis is an important factor when interpreting results of relationship and population structure, but some degree of uncertainty exists when assessing the relationship of breed composition to performance.